CITRA PEREMPUAN DALAM PUISI “JERITAN PEREMPUAN YANG MELAWAN” KARYA NOLINIA ZEGA - Kamila, Ana Tasya; Adawiyah, Siti; Julianto, Indra Rasyid (PT. CASA CENDEKIA MEDIA, 2025)
This research aims to foster awareness of the deep meaning contained in the poem